Pengaruh Program Parenting Terhadap Perilaku Belajar Siswa di SDIT Insan Madani Kota Palopo - Muamalah, Putri; Taqwa, Taqwa; Rahmadani, Ervi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this research is to determine the effect of parenting programs on students’ learning behavior at SDIT Insan Madani Palopo City. This study employed an ex-post facto research design with a quantitative approach. The population of this study consisted of fifth- and sixth-grade teachers, parents, and students at SDIT Insan Madani Palopo City. The sampling technique used was stratified random sampling, resulting in a total sample of 198 respondents, comprising 12 teachers, 93 students, and 93 parents. Data were collected through questionnaires, interviews, observations, and documentation. The research instruments used a Likert scale and were tested for validity and reliability, with all items proven to be valid and reliable. Data analysis was conducted using simple linear regression analysis with the assistance of SPSS version 23. The results of the study indicate that parenting programs have a significant effect on students’ learning behavior. The t-test results show that the t-value of 7.298 is greater than the t-table value of 1.986, with a significance value of 0.000 < 0.05, indicating that the hypothesis is accepted. The coefficient of determination (R²) value of 0.369 indicates that parenting programs contribute 36.9% to variations in students’ learning behavior, while the remaining percentage is influenced by other factors outside this study. Therefore, it can be concluded that the better the implementation of parenting programs, the better the students’ learning behavior at SDIT Insan Madani Palopo City.